# Theory Legacy_GCD

Up to index of Isabelle/HOL/Free-Groups

theory Legacy_GCD
imports Main
`(*  Title:      HOL/Old_Number_Theory/Legacy_GCD.thy    Author:     Christophe Tabacznyj and Lawrence C Paulson    Copyright   1996  University of Cambridge*)header {* The Greatest Common Divisor *}theory Legacy_GCDimports Mainbegintext {*  See \cite{davenport92}. \bigskip*}subsection {* Specification of GCD on nats *}definition  is_gcd :: "nat => nat => nat => bool" where -- {* @{term gcd} as a relation *}  "is_gcd m n p <-> p dvd m ∧ p dvd n ∧    (∀d. d dvd m --> d dvd n --> d dvd p)"text {* Uniqueness *}lemma is_gcd_unique: "is_gcd a b m ==> is_gcd a b n ==> m = n"  by (simp add: is_gcd_def) (blast intro: dvd_antisym)text {* Connection to divides relation *}lemma is_gcd_dvd: "is_gcd a b m ==> k dvd a ==> k dvd b ==> k dvd m"  by (auto simp add: is_gcd_def)text {* Commutativity *}lemma is_gcd_commute: "is_gcd m n k = is_gcd n m k"  by (auto simp add: is_gcd_def)subsection {* GCD on nat by Euclid's algorithm *}fun gcd :: "nat => nat => nat"  where "gcd m n = (if n = 0 then m else gcd n (m mod n))"lemma gcd_induct [case_names "0" rec]:  fixes m n :: nat  assumes "!!m. P m 0"    and "!!m n. 0 < n ==> P n (m mod n) ==> P m n"  shows "P m n"proof (induct m n rule: gcd.induct)  case (1 m n)  with assms show ?case by (cases "n = 0") simp_allqedlemma gcd_0 [simp, algebra]: "gcd m 0 = m"  by simplemma gcd_0_left [simp,algebra]: "gcd 0 m = m"  by simplemma gcd_non_0: "n > 0 ==> gcd m n = gcd n (m mod n)"  by simplemma gcd_1 [simp, algebra]: "gcd m (Suc 0) = Suc 0"  by simplemma nat_gcd_1_right [simp, algebra]: "gcd m 1 = 1"  unfolding One_nat_def by (rule gcd_1)declare gcd.simps [simp del]text {*  \medskip @{term "gcd m n"} divides @{text m} and @{text n}.  The  conjunctions don't seem provable separately.*}lemma gcd_dvd1 [iff, algebra]: "gcd m n dvd m"  and gcd_dvd2 [iff, algebra]: "gcd m n dvd n"  apply (induct m n rule: gcd_induct)     apply (simp_all add: gcd_non_0)  apply (blast dest: dvd_mod_imp_dvd)  donetext {*  \medskip Maximality: for all @{term m}, @{term n}, @{term k}  naturals, if @{term k} divides @{term m} and @{term k} divides  @{term n} then @{term k} divides @{term "gcd m n"}.*}lemma gcd_greatest: "k dvd m ==> k dvd n ==> k dvd gcd m n"  by (induct m n rule: gcd_induct) (simp_all add: gcd_non_0 dvd_mod)text {*  \medskip Function gcd yields the Greatest Common Divisor.*}lemma is_gcd: "is_gcd m n (gcd m n) "  by (simp add: is_gcd_def gcd_greatest)subsection {* Derived laws for GCD *}lemma gcd_greatest_iff [iff, algebra]: "k dvd gcd m n <-> k dvd m ∧ k dvd n"  by (blast intro!: gcd_greatest intro: dvd_trans)lemma gcd_zero[algebra]: "gcd m n = 0 <-> m = 0 ∧ n = 0"  by (simp only: dvd_0_left_iff [symmetric] gcd_greatest_iff)lemma gcd_commute: "gcd m n = gcd n m"  apply (rule is_gcd_unique)   apply (rule is_gcd)  apply (subst is_gcd_commute)  apply (simp add: is_gcd)  donelemma gcd_assoc: "gcd (gcd k m) n = gcd k (gcd m n)"  apply (rule is_gcd_unique)   apply (rule is_gcd)  apply (simp add: is_gcd_def)  apply (blast intro: dvd_trans)  donelemma gcd_1_left [simp, algebra]: "gcd (Suc 0) m = Suc 0"  by (simp add: gcd_commute)lemma nat_gcd_1_left [simp, algebra]: "gcd 1 m = 1"  unfolding One_nat_def by (rule gcd_1_left)text {*  \medskip Multiplication laws*}lemma gcd_mult_distrib2: "k * gcd m n = gcd (k * m) (k * n)"    -- {* \cite[page 27]{davenport92} *}  apply (induct m n rule: gcd_induct)   apply simp  apply (case_tac "k = 0")   apply (simp_all add: gcd_non_0)  donelemma gcd_mult [simp, algebra]: "gcd k (k * n) = k"  apply (rule gcd_mult_distrib2 [of k 1 n, simplified, symmetric])  donelemma gcd_self [simp, algebra]: "gcd k k = k"  apply (rule gcd_mult [of k 1, simplified])  donelemma relprime_dvd_mult: "gcd k n = 1 ==> k dvd m * n ==> k dvd m"  apply (insert gcd_mult_distrib2 [of m k n])  apply simp  apply (erule_tac t = m in ssubst)  apply simp  donelemma relprime_dvd_mult_iff: "gcd k n = 1 ==> (k dvd m * n) = (k dvd m)"  by (auto intro: relprime_dvd_mult dvd_mult2)lemma gcd_mult_cancel: "gcd k n = 1 ==> gcd (k * m) n = gcd m n"  apply (rule dvd_antisym)   apply (rule gcd_greatest)    apply (rule_tac n = k in relprime_dvd_mult)     apply (simp add: gcd_assoc)     apply (simp add: gcd_commute)    apply (simp_all add: mult_commute)  donetext {* \medskip Addition laws *}lemma gcd_add1 [simp, algebra]: "gcd (m + n) n = gcd m n"  by (cases "n = 0") (auto simp add: gcd_non_0)lemma gcd_add2 [simp, algebra]: "gcd m (m + n) = gcd m n"proof -  have "gcd m (m + n) = gcd (m + n) m" by (rule gcd_commute)  also have "... = gcd (n + m) m" by (simp add: add_commute)  also have "... = gcd n m" by simp  also have  "... = gcd m n" by (rule gcd_commute)  finally show ?thesis .qedlemma gcd_add2' [simp, algebra]: "gcd m (n + m) = gcd m n"  apply (subst add_commute)  apply (rule gcd_add2)  donelemma gcd_add_mult[algebra]: "gcd m (k * m + n) = gcd m n"  by (induct k) (simp_all add: add_assoc)lemma gcd_dvd_prod: "gcd m n dvd m * n"   using mult_dvd_mono [of 1] by autotext {*  \medskip Division by gcd yields rrelatively primes.*}lemma div_gcd_relprime:  assumes nz: "a ≠ 0 ∨ b ≠ 0"  shows "gcd (a div gcd a b) (b div gcd a b) = 1"proof -  let ?g = "gcd a b"  let ?a' = "a div ?g"  let ?b' = "b div ?g"  let ?g' = "gcd ?a' ?b'"  have dvdg: "?g dvd a" "?g dvd b" by simp_all  have dvdg': "?g' dvd ?a'" "?g' dvd ?b'" by simp_all  from dvdg dvdg' obtain ka kb ka' kb' where      kab: "a = ?g * ka" "b = ?g * kb" "?a' = ?g' * ka'" "?b' = ?g' * kb'"    unfolding dvd_def by blast  then have "?g * ?a' = (?g * ?g') * ka'" "?g * ?b' = (?g * ?g') * kb'" by simp_all  then have dvdgg':"?g * ?g' dvd a" "?g* ?g' dvd b"    by (auto simp add: dvd_mult_div_cancel [OF dvdg(1)]      dvd_mult_div_cancel [OF dvdg(2)] dvd_def)  have "?g ≠ 0" using nz by (simp add: gcd_zero)  then have gp: "?g > 0" by simp  from gcd_greatest [OF dvdgg'] have "?g * ?g' dvd ?g" .  with dvd_mult_cancel1 [OF gp] show "?g' = 1" by simpqedlemma gcd_unique: "d dvd a∧d dvd b ∧ (∀e. e dvd a ∧ e dvd b --> e dvd d) <-> d = gcd a b"proof(auto)  assume H: "d dvd a" "d dvd b" "∀e. e dvd a ∧ e dvd b --> e dvd d"  from H(3)[rule_format] gcd_dvd1[of a b] gcd_dvd2[of a b]   have th: "gcd a b dvd d" by blast  from dvd_antisym[OF th gcd_greatest[OF H(1,2)]]  show "d = gcd a b" by blast qedlemma gcd_eq: assumes H: "∀d. d dvd x ∧ d dvd y <-> d dvd u ∧ d dvd v"  shows "gcd x y = gcd u v"proof-  from H have "∀d. d dvd x ∧ d dvd y <-> d dvd gcd u v" by simp  with gcd_unique[of "gcd u v" x y]  show ?thesis by autoqedlemma ind_euclid:  assumes c: " ∀a b. P (a::nat) b <-> P b a" and z: "∀a. P a 0"  and add: "∀a b. P a b --> P a (a + b)"  shows "P a b"proof(induct "a + b" arbitrary: a b rule: less_induct)  case less  have "a = b ∨ a < b ∨ b < a" by arith  moreover {assume eq: "a= b"    from add[rule_format, OF z[rule_format, of a]] have "P a b" using eq    by simp}  moreover  {assume lt: "a < b"    hence "a + b - a < a + b ∨ a = 0" by arith    moreover    {assume "a =0" with z c have "P a b" by blast }    moreover    {assume "a + b - a < a + b"      also have th0: "a + b - a = a + (b - a)" using lt by arith      finally have "a + (b - a) < a + b" .      then have "P a (a + (b - a))" by (rule add[rule_format, OF less])      then have "P a b" by (simp add: th0[symmetric])}    ultimately have "P a b" by blast}  moreover  {assume lt: "a > b"    hence "b + a - b < a + b ∨ b = 0" by arith    moreover    {assume "b =0" with z c have "P a b" by blast }    moreover    {assume "b + a - b < a + b"      also have th0: "b + a - b = b + (a - b)" using lt by arith      finally have "b + (a - b) < a + b" .      then have "P b (b + (a - b))" by (rule add[rule_format, OF less])      then have "P b a" by (simp add: th0[symmetric])      hence "P a b" using c by blast }    ultimately have "P a b" by blast}ultimately  show "P a b" by blastqedlemma bezout_lemma:   assumes ex: "∃(d::nat) x y. d dvd a ∧ d dvd b ∧ (a * x = b * y + d ∨ b * x = a * y + d)"  shows "∃d x y. d dvd a ∧ d dvd a + b ∧ (a * x = (a + b) * y + d ∨ (a + b) * x = a * y + d)"using exapply clarsimpapply (rule_tac x="d" in exI, simp)apply (case_tac "a * x = b * y + d" , simp_all)apply (rule_tac x="x + y" in exI)apply (rule_tac x="y" in exI)apply algebraapply (rule_tac x="x" in exI)apply (rule_tac x="x + y" in exI)apply algebradonelemma bezout_add: "∃(d::nat) x y. d dvd a ∧ d dvd b ∧ (a * x = b * y + d ∨ b * x = a * y + d)"apply(induct a b rule: ind_euclid)apply blastapply clarifyapply (rule_tac x="a" in exI, simp)apply clarsimpapply (rule_tac x="d" in exI)apply (case_tac "a * x = b * y + d", simp_all)apply (rule_tac x="x+y" in exI)apply (rule_tac x="y" in exI)apply algebraapply (rule_tac x="x" in exI)apply (rule_tac x="x+y" in exI)apply algebradonelemma bezout: "∃(d::nat) x y. d dvd a ∧ d dvd b ∧ (a * x - b * y = d ∨ b * x - a * y = d)"using bezout_add[of a b]apply clarsimpapply (rule_tac x="d" in exI, simp)apply (rule_tac x="x" in exI)apply (rule_tac x="y" in exI)apply autodonetext {* We can get a stronger version with a nonzeroness assumption. *}lemma divides_le: "m dvd n ==> m <= n ∨ n = (0::nat)" by (auto simp add: dvd_def)lemma bezout_add_strong: assumes nz: "a ≠ (0::nat)"  shows "∃d x y. d dvd a ∧ d dvd b ∧ a * x = b * y + d"proof-  from nz have ap: "a > 0" by simp from bezout_add[of a b]  have "(∃d x y. d dvd a ∧ d dvd b ∧ a * x = b * y + d) ∨ (∃d x y. d dvd a ∧ d dvd b ∧ b * x = a * y + d)" by blast moreover {fix d x y assume H: "d dvd a" "d dvd b" "a * x = b * y + d"   from H have ?thesis by blast } moreover {fix d x y assume H: "d dvd a" "d dvd b" "b * x = a * y + d"   {assume b0: "b = 0" with H  have ?thesis by simp}   moreover    {assume b: "b ≠ 0" hence bp: "b > 0" by simp     from divides_le[OF H(2)] b have "d < b ∨ d = b" using le_less by blast     moreover     {assume db: "d=b"       from nz H db have ?thesis apply simp         apply (rule exI[where x = b], simp)         apply (rule exI[where x = b])        by (rule exI[where x = "a - 1"], simp add: diff_mult_distrib2)}    moreover    {assume db: "d < b"         {assume "x=0" hence ?thesis using nz H by simp }        moreover        {assume x0: "x ≠ 0" hence xp: "x > 0" by simp                    from db have "d ≤ b - 1" by simp          hence "d*b ≤ b*(b - 1)" by simp          with xp mult_mono[of "1" "x" "d*b" "b*(b - 1)"]          have dble: "d*b ≤ x*b*(b - 1)" using bp by simp          from H (3) have "a * ((b - 1) * y) + d * (b - 1 + 1) = d + x*b*(b - 1)" by algebra          hence "a * ((b - 1) * y) = d + x*b*(b - 1) - d*b" using bp by simp          hence "a * ((b - 1) * y) = d + (x*b*(b - 1) - d*b)"             by (simp only: diff_add_assoc[OF dble, of d, symmetric])          hence "a * ((b - 1) * y) = b*(x*(b - 1) - d) + d"            by (simp only: diff_mult_distrib2 add_commute mult_ac)          hence ?thesis using H(1,2)            apply -            apply (rule exI[where x=d], simp)            apply (rule exI[where x="(b - 1) * y"])            by (rule exI[where x="x*(b - 1) - d"], simp)}        ultimately have ?thesis by blast}    ultimately have ?thesis by blast}  ultimately have ?thesis by blast} ultimately show ?thesis by blastqedlemma bezout_gcd: "∃x y. a * x - b * y = gcd a b ∨ b * x - a * y = gcd a b"proof-  let ?g = "gcd a b"  from bezout[of a b] obtain d x y where d: "d dvd a" "d dvd b" "a * x - b * y = d ∨ b * x - a * y = d" by blast  from d(1,2) have "d dvd ?g" by simp  then obtain k where k: "?g = d*k" unfolding dvd_def by blast  from d(3) have "(a * x - b * y)*k = d*k ∨ (b * x - a * y)*k = d*k" by blast   hence "a * x * k - b * y*k = d*k ∨ b * x * k - a * y*k = d*k"     by (algebra add: diff_mult_distrib)  hence "a * (x * k) - b * (y*k) = ?g ∨ b * (x * k) - a * (y*k) = ?g"     by (simp add: k mult_assoc)  thus ?thesis by blastqedlemma bezout_gcd_strong: assumes a: "a ≠ 0"   shows "∃x y. a * x = b * y + gcd a b"proof-  let ?g = "gcd a b"  from bezout_add_strong[OF a, of b]  obtain d x y where d: "d dvd a" "d dvd b" "a * x = b * y + d" by blast  from d(1,2) have "d dvd ?g" by simp  then obtain k where k: "?g = d*k" unfolding dvd_def by blast  from d(3) have "a * x * k = (b * y + d) *k " by algebra  hence "a * (x * k) = b * (y*k) + ?g" by (algebra add: k)  thus ?thesis by blastqedlemma gcd_mult_distrib: "gcd(a * c) (b * c) = c * gcd a b"by(simp add: gcd_mult_distrib2 mult_commute)lemma gcd_bezout: "(∃x y. a * x - b * y = d ∨ b * x - a * y = d) <-> gcd a b dvd d"  (is "?lhs <-> ?rhs")proof-  let ?g = "gcd a b"  {assume H: ?rhs then obtain k where k: "d = ?g*k" unfolding dvd_def by blast    from bezout_gcd[of a b] obtain x y where xy: "a * x - b * y = ?g ∨ b * x - a * y = ?g"      by blast    hence "(a * x - b * y)*k = ?g*k ∨ (b * x - a * y)*k = ?g*k" by auto    hence "a * x*k - b * y*k = ?g*k ∨ b * x * k - a * y*k = ?g*k"       by (simp only: diff_mult_distrib)    hence "a * (x*k) - b * (y*k) = d ∨ b * (x * k) - a * (y*k) = d"      by (simp add: k[symmetric] mult_assoc)    hence ?lhs by blast}  moreover  {fix x y assume H: "a * x - b * y = d ∨ b * x - a * y = d"    have dv: "?g dvd a*x" "?g dvd b * y" "?g dvd b*x" "?g dvd a * y"      using dvd_mult2[OF gcd_dvd1[of a b]] dvd_mult2[OF gcd_dvd2[of a b]] by simp_all    from dvd_diff_nat[OF dv(1,2)] dvd_diff_nat[OF dv(3,4)] H    have ?rhs by auto}  ultimately show ?thesis by blastqedlemma gcd_bezout_sum: assumes H:"a * x + b * y = d" shows "gcd a b dvd d"proof-  let ?g = "gcd a b"    have dv: "?g dvd a*x" "?g dvd b * y"       using dvd_mult2[OF gcd_dvd1[of a b]] dvd_mult2[OF gcd_dvd2[of a b]] by simp_all    from dvd_add[OF dv] H    show ?thesis by autoqedlemma gcd_mult': "gcd b (a * b) = b"by (simp add: mult_commute[of a b]) lemma gcd_add: "gcd(a + b) b = gcd a b"   "gcd(b + a) b = gcd a b" "gcd a (a + b) = gcd a b" "gcd a (b + a) = gcd a b"by (simp_all add: gcd_commute)lemma gcd_sub: "b <= a ==> gcd(a - b) b = gcd a b" "a <= b ==> gcd a (b - a) = gcd a b"proof-  {fix a b assume H: "b ≤ (a::nat)"    hence th: "a - b + b = a" by arith    from gcd_add(1)[of "a - b" b] th  have "gcd(a - b) b = gcd a b" by simp}  note th = this{  assume ab: "b ≤ a"  from th[OF ab] show "gcd (a - b)  b = gcd a b" by blastnext  assume ab: "a ≤ b"  from th[OF ab] show "gcd a (b - a) = gcd a b"     by (simp add: gcd_commute)}qedsubsection {* LCM defined by GCD *}definition  lcm :: "nat => nat => nat"where  lcm_def: "lcm m n = m * n div gcd m n"lemma prod_gcd_lcm:  "m * n = gcd m n * lcm m n"  unfolding lcm_def by (simp add: dvd_mult_div_cancel [OF gcd_dvd_prod])lemma lcm_0 [simp]: "lcm m 0 = 0"  unfolding lcm_def by simplemma lcm_1 [simp]: "lcm m 1 = m"  unfolding lcm_def by simplemma lcm_0_left [simp]: "lcm 0 n = 0"  unfolding lcm_def by simplemma lcm_1_left [simp]: "lcm 1 m = m"  unfolding lcm_def by simplemma dvd_pos:  fixes n m :: nat  assumes "n > 0" and "m dvd n"  shows "m > 0"using assms by (cases m) autolemma lcm_least:  assumes "m dvd k" and "n dvd k"  shows "lcm m n dvd k"proof (cases k)  case 0 then show ?thesis by autonext  case (Suc _) then have pos_k: "k > 0" by auto  from assms dvd_pos [OF this] have pos_mn: "m > 0" "n > 0" by auto  with gcd_zero [of m n] have pos_gcd: "gcd m n > 0" by simp  from assms obtain p where k_m: "k = m * p" using dvd_def by blast  from assms obtain q where k_n: "k = n * q" using dvd_def by blast  from pos_k k_m have pos_p: "p > 0" by auto  from pos_k k_n have pos_q: "q > 0" by auto  have "k * k * gcd q p = k * gcd (k * q) (k * p)"    by (simp add: mult_ac gcd_mult_distrib2)  also have "… = k * gcd (m * p * q) (n * q * p)"    by (simp add: k_m [symmetric] k_n [symmetric])  also have "… = k * p * q * gcd m n"    by (simp add: mult_ac gcd_mult_distrib2)  finally have "(m * p) * (n * q) * gcd q p = k * p * q * gcd m n"    by (simp only: k_m [symmetric] k_n [symmetric])  then have "p * q * m * n * gcd q p = p * q * k * gcd m n"    by (simp add: mult_ac)  with pos_p pos_q have "m * n * gcd q p = k * gcd m n"    by simp  with prod_gcd_lcm [of m n]  have "lcm m n * gcd q p * gcd m n = k * gcd m n"    by (simp add: mult_ac)  with pos_gcd have "lcm m n * gcd q p = k" by simp  then show ?thesis using dvd_def by autoqedlemma lcm_dvd1 [iff]:  "m dvd lcm m n"proof (cases m)  case 0 then show ?thesis by simpnext  case (Suc _)  then have mpos: "m > 0" by simp  show ?thesis  proof (cases n)    case 0 then show ?thesis by simp  next    case (Suc _)    then have npos: "n > 0" by simp    have "gcd m n dvd n" by simp    then obtain k where "n = gcd m n * k" using dvd_def by auto    then have "m * n div gcd m n = m * (gcd m n * k) div gcd m n" by (simp add: mult_ac)    also have "… = m * k" using mpos npos gcd_zero by simp    finally show ?thesis by (simp add: lcm_def)  qedqedlemma lcm_dvd2 [iff]:   "n dvd lcm m n"proof (cases n)  case 0 then show ?thesis by simpnext  case (Suc _)  then have npos: "n > 0" by simp  show ?thesis  proof (cases m)    case 0 then show ?thesis by simp  next    case (Suc _)    then have mpos: "m > 0" by simp    have "gcd m n dvd m" by simp    then obtain k where "m = gcd m n * k" using dvd_def by auto    then have "m * n div gcd m n = (gcd m n * k) * n div gcd m n" by (simp add: mult_ac)    also have "… = n * k" using mpos npos gcd_zero by simp    finally show ?thesis by (simp add: lcm_def)  qedqedlemma gcd_add1_eq: "gcd (m + k) k = gcd (m + k) m"  by (simp add: gcd_commute)lemma gcd_diff2: "m ≤ n ==> gcd n (n - m) = gcd n m"  apply (subgoal_tac "n = m + (n - m)")  apply (erule ssubst, rule gcd_add1_eq, simp)    donesubsection {* GCD and LCM on integers *}definition  zgcd :: "int => int => int" where  "zgcd i j = int (gcd (nat (abs i)) (nat (abs j)))"lemma zgcd_zdvd1 [iff, algebra]: "zgcd i j dvd i"by (simp add: zgcd_def int_dvd_iff)lemma zgcd_zdvd2 [iff, algebra]: "zgcd i j dvd j"by (simp add: zgcd_def int_dvd_iff)lemma zgcd_pos: "zgcd i j ≥ 0"by (simp add: zgcd_def)lemma zgcd0 [simp,algebra]: "(zgcd i j = 0) = (i = 0 ∧ j = 0)"by (simp add: zgcd_def gcd_zero)lemma zgcd_commute: "zgcd i j = zgcd j i"unfolding zgcd_def by (simp add: gcd_commute)lemma zgcd_zminus [simp, algebra]: "zgcd (- i) j = zgcd i j"unfolding zgcd_def by simplemma zgcd_zminus2 [simp, algebra]: "zgcd i (- j) = zgcd i j"unfolding zgcd_def by simp  (* should be solved by algebra*)lemma zrelprime_dvd_mult: "zgcd i j = 1 ==> i dvd k * j ==> i dvd k"  unfolding zgcd_defproof -  assume "int (gcd (nat ¦i¦) (nat ¦j¦)) = 1" "i dvd k * j"  then have g: "gcd (nat ¦i¦) (nat ¦j¦) = 1" by simp  from `i dvd k * j` obtain h where h: "k*j = i*h" unfolding dvd_def by blast  have th: "nat ¦i¦ dvd nat ¦k¦ * nat ¦j¦"    unfolding dvd_def    by (rule_tac x= "nat ¦h¦" in exI, simp add: h nat_abs_mult_distrib [symmetric])  from relprime_dvd_mult [OF g th] obtain h' where h': "nat ¦k¦ = nat ¦i¦ * h'"    unfolding dvd_def by blast  from h' have "int (nat ¦k¦) = int (nat ¦i¦ * h')" by simp  then have "¦k¦ = ¦i¦ * int h'" by (simp add: int_mult)  then show ?thesis    apply (subst abs_dvd_iff [symmetric])    apply (subst dvd_abs_iff [symmetric])    apply (unfold dvd_def)    apply (rule_tac x = "int h'" in exI, simp)    doneqedlemma int_nat_abs: "int (nat (abs x)) = abs x" by arithlemma zgcd_greatest:  assumes "k dvd m" and "k dvd n"  shows "k dvd zgcd m n"proof -  let ?k' = "nat ¦k¦"  let ?m' = "nat ¦m¦"  let ?n' = "nat ¦n¦"  from `k dvd m` and `k dvd n` have dvd': "?k' dvd ?m'" "?k' dvd ?n'"    unfolding zdvd_int by (simp_all only: int_nat_abs abs_dvd_iff dvd_abs_iff)  from gcd_greatest [OF dvd'] have "int (nat ¦k¦) dvd zgcd m n"    unfolding zgcd_def by (simp only: zdvd_int)  then have "¦k¦ dvd zgcd m n" by (simp only: int_nat_abs)  then show "k dvd zgcd m n" by simpqedlemma div_zgcd_relprime:  assumes nz: "a ≠ 0 ∨ b ≠ 0"  shows "zgcd (a div (zgcd a b)) (b div (zgcd a b)) = 1"proof -  from nz have nz': "nat ¦a¦ ≠ 0 ∨ nat ¦b¦ ≠ 0" by arith   let ?g = "zgcd a b"  let ?a' = "a div ?g"  let ?b' = "b div ?g"  let ?g' = "zgcd ?a' ?b'"  have dvdg: "?g dvd a" "?g dvd b" by simp_all  have dvdg': "?g' dvd ?a'" "?g' dvd ?b'" by simp_all  from dvdg dvdg' obtain ka kb ka' kb' where   kab: "a = ?g*ka" "b = ?g*kb" "?a' = ?g'*ka'" "?b' = ?g' * kb'"    unfolding dvd_def by blast  then have "?g* ?a' = (?g * ?g') * ka'" "?g* ?b' = (?g * ?g') * kb'" by simp_all  then have dvdgg':"?g * ?g' dvd a" "?g* ?g' dvd b"    by (auto simp add: dvd_mult_div_cancel [OF dvdg(1)]      dvd_mult_div_cancel [OF dvdg(2)] dvd_def)  have "?g ≠ 0" using nz by simp  then have gp: "?g ≠ 0" using zgcd_pos[where i="a" and j="b"] by arith  from zgcd_greatest [OF dvdgg'] have "?g * ?g' dvd ?g" .  with zdvd_mult_cancel1 [OF gp] have "¦?g'¦ = 1" by simp  with zgcd_pos show "?g' = 1" by simpqedlemma zgcd_0 [simp, algebra]: "zgcd m 0 = abs m"  by (simp add: zgcd_def abs_if)lemma zgcd_0_left [simp, algebra]: "zgcd 0 m = abs m"  by (simp add: zgcd_def abs_if)lemma zgcd_non_0: "0 < n ==> zgcd m n = zgcd n (m mod n)"  apply (frule_tac b = n and a = m in pos_mod_sign)  apply (simp del: pos_mod_sign add: zgcd_def abs_if nat_mod_distrib)  apply (auto simp add: gcd_non_0 nat_mod_distrib [symmetric] zmod_zminus1_eq_if)  apply (frule_tac a = m in pos_mod_bound)  apply (simp del: pos_mod_bound add: nat_diff_distrib gcd_diff2 nat_le_eq_zle)  donelemma zgcd_eq: "zgcd m n = zgcd n (m mod n)"  apply (cases "n = 0", simp)  apply (auto simp add: linorder_neq_iff zgcd_non_0)  apply (cut_tac m = "-m" and n = "-n" in zgcd_non_0, auto)  donelemma zgcd_1 [simp, algebra]: "zgcd m 1 = 1"  by (simp add: zgcd_def abs_if)lemma zgcd_0_1_iff [simp, algebra]: "zgcd 0 m = 1 <-> ¦m¦ = 1"  by (simp add: zgcd_def abs_if)lemma zgcd_greatest_iff[algebra]: "k dvd zgcd m n = (k dvd m ∧ k dvd n)"  by (simp add: zgcd_def abs_if int_dvd_iff dvd_int_iff nat_dvd_iff)lemma zgcd_1_left [simp, algebra]: "zgcd 1 m = 1"  by (simp add: zgcd_def)lemma zgcd_assoc: "zgcd (zgcd k m) n = zgcd k (zgcd m n)"  by (simp add: zgcd_def gcd_assoc)lemma zgcd_left_commute: "zgcd k (zgcd m n) = zgcd m (zgcd k n)"  apply (rule zgcd_commute [THEN trans])  apply (rule zgcd_assoc [THEN trans])  apply (rule zgcd_commute [THEN arg_cong])  donelemmas zgcd_ac = zgcd_assoc zgcd_commute zgcd_left_commute  -- {* addition is an AC-operator *}lemma zgcd_zmult_distrib2: "0 ≤ k ==> k * zgcd m n = zgcd (k * m) (k * n)"  by (simp del: minus_mult_right [symmetric]      add: minus_mult_right nat_mult_distrib zgcd_def abs_if          mult_less_0_iff gcd_mult_distrib2 [symmetric] of_nat_mult)lemma zgcd_zmult_distrib2_abs: "zgcd (k * m) (k * n) = abs k * zgcd m n"  by (simp add: abs_if zgcd_zmult_distrib2)lemma zgcd_self [simp]: "0 ≤ m ==> zgcd m m = m"  by (cut_tac k = m and m = 1 and n = 1 in zgcd_zmult_distrib2, simp_all)lemma zgcd_zmult_eq_self [simp]: "0 ≤ k ==> zgcd k (k * n) = k"  by (cut_tac k = k and m = 1 and n = n in zgcd_zmult_distrib2, simp_all)lemma zgcd_zmult_eq_self2 [simp]: "0 ≤ k ==> zgcd (k * n) k = k"  by (cut_tac k = k and m = n and n = 1 in zgcd_zmult_distrib2, simp_all)definition "zlcm i j = int (lcm(nat(abs i)) (nat(abs j)))"lemma dvd_zlcm_self1[simp, algebra]: "i dvd zlcm i j"by(simp add:zlcm_def dvd_int_iff)lemma dvd_zlcm_self2[simp, algebra]: "j dvd zlcm i j"by(simp add:zlcm_def dvd_int_iff)lemma dvd_imp_dvd_zlcm1:  assumes "k dvd i" shows "k dvd (zlcm i j)"proof -  have "nat(abs k) dvd nat(abs i)" using `k dvd i`    by(simp add:int_dvd_iff[symmetric] dvd_int_iff[symmetric])  thus ?thesis by(simp add:zlcm_def dvd_int_iff)(blast intro: dvd_trans)qedlemma dvd_imp_dvd_zlcm2:  assumes "k dvd j" shows "k dvd (zlcm i j)"proof -  have "nat(abs k) dvd nat(abs j)" using `k dvd j`    by(simp add:int_dvd_iff[symmetric] dvd_int_iff[symmetric])  thus ?thesis by(simp add:zlcm_def dvd_int_iff)(blast intro: dvd_trans)qedlemma zdvd_self_abs1: "(d::int) dvd (abs d)"by (case_tac "d <0", simp_all)lemma zdvd_self_abs2: "(abs (d::int)) dvd d"by (case_tac "d<0", simp_all)(* lcm a b is positive for positive a and b *)lemma lcm_pos:   assumes mpos: "m > 0"    and npos: "n>0"  shows "lcm m n > 0"proof (rule ccontr, simp add: lcm_def gcd_zero)  assume h:"m*n div gcd m n = 0"  from mpos npos have "gcd m n ≠ 0" using gcd_zero by simp  hence gcdp: "gcd m n > 0" by simp  with h  have "m*n < gcd m n"    by (cases "m * n < gcd m n") (auto simp add: div_if[OF gcdp, where m="m*n"])  moreover   have "gcd m n dvd m" by simp  with mpos dvd_imp_le have t1:"gcd m n ≤ m" by simp  with npos have t1:"gcd m n *n ≤ m*n" by simp  have "gcd m n ≤ gcd m n*n" using npos by simp  with t1 have "gcd m n ≤ m*n" by arith  ultimately show "False" by simpqedlemma zlcm_pos:   assumes anz: "a ≠ 0"  and bnz: "b ≠ 0"   shows "0 < zlcm a b"proof-  let ?na = "nat (abs a)"  let ?nb = "nat (abs b)"  have nap: "?na >0" using anz by simp  have nbp: "?nb >0" using bnz by simp  have "0 < lcm ?na ?nb" by (rule lcm_pos[OF nap nbp])  thus ?thesis by (simp add: zlcm_def)qedlemma zgcd_code [code]:  "zgcd k l = ¦if l = 0 then k else zgcd l (¦k¦ mod ¦l¦)¦"  by (simp add: zgcd_def gcd.simps [of "nat ¦k¦"] nat_mod_distrib)end`